Psychosocial Determinants of Tobacco Use among School Going Adolescents in Delhi, India - Kumar, Varun (J Addict, 2014)
Background. Tobacco use is one of the major preventable causes of premature death and disease in the world. Many psychosocial factors were found to influence tobacco use. Therefore the present study was designed to determine the role of psychosocial factors associated with tobacco use among school going adolescents in Delhi, India. Methods. Cross-sectional study was conducted from February 2013 to September 2013 in four government schools in South district of Delhi, India. The questionnaire contains questions adapted from GYTS (Global Youth Tobacco Survey) to find the prevalence and pattern of tobacco use among adolescents. Data were analyzed using SPSS version 21. Results. The prevalence of ever and current tobacco use was found in 16.4% and 13.1%. Current smoking and current tobacco chewing were found in 10.2% and 9.4% students, respectively. The risk of current tobacco use was found to be higher among males (P value = 0.000) and in those who got higher pocket money (P value = 0.000). Psychosocial factors like lower general self-efficacy and maladjustments with peers, teachers, and schools were also found to be significant predictors of current tobacco use. Conclusion. The study has revealed higher prevalence of ever and current tobacco use among adolescent students in Delhi, India.